The Effect of Booklet Media Education on Reducing Blood Sugar Levels in Type 2 Diabetes Mellitus Patients in the Telaga Biru Health Center Work Area - Nurliah Nurliah; Andi Akifa Sudirman; Miftahuljanah Hinelo (Universitas Ibn Khaldun Bogor, 2023)
Diabetes Mellitus is a chronic disease that is a challenge in the world of health. This study aims to determine the effect of booklet media education on reducing blood sugar levels in patients with type 2 diabetes mellitus. The study used a quantitative approach. This research is a type of quasi-experimental research with one group pre-test-post test design. The sample was taken by systematic random sampling technique with a sample of 30 respondents. Data collection using observation sheets and data analysis using the Wilcoxon test with a meaning level of 95% (a = 0.05). The results of the study showed that blood sugar levels decreased from Pre-Test to Post-Test with Mean Ranks of 13.50 and statistical test results were obtained p = 0.00p (p < 0.05) so that it can be concluded that there is an influence of booklet media education on reducing blood sugar levels in patients with type 2 diabetes mellitus.